LABYRINTH AND EQUILIBRIUM : I. A COMPARISON OF THE EFFECT OF REMOVAL OF THE OTOLITH ORGANS AND OF THE SEMICIRCULAR CANALS. - Maxwell, S. S. (The Rockefeller University Press, 1919)
1. A dogfish from which all six ampullæ have been removed maintains its equilibrium; the righting reactions occur promptly; compensatory movements of the eyes occur in response to rotations in all planes except the horizontal; the compensatory position of the eyes is retained if the animal is held in an abnormal position. Both the static and dynamic functions of equilibrium continue, therefore, after complete removal of all the semicircular canals and all the ampullæ. 2. After complete removal of the otoliths from the vestibules without injury to the ampullæ the animal maintains its equilibrium in the water, rights itself promptly, and makes compensatory motions to rotations in all planes. If held in an abnormal position the compensatory position of the eyes is maintained. Both static and dynamic functions of equilibrium continue. 3. Destruction of both the semicircular canals and the otolith organs completely abolishes all compensatory movements and equilibrium reactions of labyrinthine origin. 4. It is pointed out that these observations do not justify the theory of Mach and Breuer that the ampullæ and semicircular canals are the organs for the dynamic functions of equilibrium, and that the otoliths are the organs for the static functions of equilibrium. 5. The new experiments recorded in this paper show that the ampullæ alone (without the otoliths) suffice for all the dynamic and all the static functions of equilibrium of the ear; and that the otolith organs (without the ampullæ) suffice for all the static and for all the dynamic functions of equilibrium of the ear with the exception of the response to a rotation of the animal in a horizontal plane.